Analisis Pembelajaran Algoritma Pemrograman di Era Covid-19 Terhadap Mahasiswa Matematika - Nazila, Ila; Yahfizham (CV. ITTC INDONESIA, 2023)
The spread of Covid-19 or commonly known as corona is a disease originating in China, Wuhan, Hubei Province. The virus is very dangerous to humans because it has deadly symptoms such as chest pain, shortness of breath, difficulty breathing and the inability to speak. The algorithm is derived from the name of the very famous Arab writer Abu Ja’far Muhammad Ibnu Musa Al- Khuwarizmi. Algorithms are closely related to mathematics and also computer science. It's a system designed to solve an existing problem. A programming algorithm is a basis or foundation designed logically and systematically, with the aim of being easily followed and implemented by a computer or other data processing system. The method used is a literary method, by collecting data from several sources. In studying algorithms we will learn about flowchart and pseudocode. Where it's expected to help all students, whether they're maths students or other students.